1986
DOI: 10.1002/ddr.430080133
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome p‐450: Target for itraconazole

Abstract: Cytochrome P-450: Target for itraconazole. Drug Dev. Res. 8:287-298, 1986.The N-substituted triazole, itraconazole, has high affinity for the cytochrome P-450 (cyt. P-450) isozyme involved in the 14a-demethylation of lanosterol in Candida albicans microsomes. Fifty per cent inhibition was already observed at itraconazole concentations < 5x lo-' M. Higher concentrations (> lo-' M) of this antifungal are needed to interfere with the 14 a-demethylation in mammalian cells. Unlike ketoconazole, itraconazole does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 12 publications
2
48
1
Order By: Relevance
“…Summaries of the toxicity and adverse reactions of itraconazole recently have been reviewed by De Coster et al (64), Van Cauteren et al (314), and Vanden Bossche et al (326,327). Subchronic toxicity studies in experimental animals demonstrated that the potential target organs for toxicity are the gastrointestinal tract, the mononuclear phagocytizing system, and the adrenals, although the activity observed was less than that seen with ketoconazole (313,314).…”
Section: Antifungal Imidazoles Under Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Summaries of the toxicity and adverse reactions of itraconazole recently have been reviewed by De Coster et al (64), Van Cauteren et al (314), and Vanden Bossche et al (326,327). Subchronic toxicity studies in experimental animals demonstrated that the potential target organs for toxicity are the gastrointestinal tract, the mononuclear phagocytizing system, and the adrenals, although the activity observed was less than that seen with ketoconazole (313,314).…”
Section: Antifungal Imidazoles Under Developmentmentioning
confidence: 99%
“…The effects of itraconazole on the pituitary-testicularadrenal axis have been studied extensively (64,326,327). Daily administration of itraconazole at 100 mg for 1 month in human volunteers revealed that basal or luteinizing hormone-releasing hormone-stimulated plasma prolactin, follicle-stimulating hormone, and luteinizing hormone concentrations were not affected.…”
Section: Antifungal Imidazoles Under Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Ketoconazole (Nizoral) inhibits steroid biosynthesis in patients as it does in fungi by inhibition of cytochrome P 450 dependent enzymes (Loose et al, 1983). Thus nizoral impairs the biosynthesis of ergosterol for the cytoplasmic membrane and lead to the accumulation of 14-α methyl sterols (Vanden Bossche et al, 1986). These methyl sterols may disrupt the close packing of acyl chains of phospholipids, impairing the function of certain membrane-bound enzyme systems and inhibiting growth of fungi (Bennett, 1991).…”
Section: Introductionmentioning
confidence: 99%